Sistem Informasi Manajemen Nikah dalam Penguatan Layanan Pencatatan Pernikahan Persfektif Siyasah Dusturiyah - Sulistiani, Sulistiani; Melani, Melani; Addi, Nabilla; Wahyuni, Ridzky; Aulia, Intan; Amaliyah, Suci; Sari, Ratna; Huda, Khoirul (UIN Sumatera Utara, 2025)
Digitalizing religious bureaucracy represents a contemporary manifestation of the state's efforts to achieve public welfare through administrative order. This study aims to analyze the implementation of the Marriage Management Information System (SIMKAH) at the Office of Religious Affairs (KUA) through the lens of Siyasah Dusturiyah (Islamic Constitutional Law). The central question explores how SIMKAH fosters service quality and ensures reliable administrative certainty for prospective brides and grooms. Employing a qualitative method, data were gathered through observation, in-depth interviews, and documentation with KUA officials. The findings demonstrate that SIMKAH plays a pivotal role in manifesting administrative professionalism (al-itqan wa al-dhabt al-idari), information transparency as a form of power entrustment (al-shafafiyyah wa al-mas’uliyyah), and accessibility of services (taysir al-khidmah) to guarantee legal certainty (al-yaqin al-qanuni). Consequently, marriage documents are not merely administrative requirements but serve as instruments to protect the public by mitigating data discrepancies and maladministration. SIMKAH is proven to have shifted the KUA service paradigm from traditional-clerical patterns toward modern, accountable, and technocratic governance. This study concludes that the digitalization of marriage registration is a fundamental foundation in strengthening the state's function to protect citizens' rights (hifdz al-huquq) in accordance with the principles of justice in Islamic constitutionalism